Regionale Einflussfaktoren auf den Ausbau erneuerbarer Energien. Ergebnisse einer Fallstudie in der Brandenburger Energieregion Lausitz. - Keppler, Dorothee (Oekom, 2007)
Welche Faktoren fördern oder hemmen aus Sicht regionaler Akteure die verstärkte Nutzung erneuerbarer Energien? Das Beispiel der Energieregion Lausitz zeigt: Förderlich wären auf regionaler Ebene etwa mehr Öffentlichkeitsarbeit oder bessere Rahmenbedingungen für Kooperationen.

Which factors shape the development of renewable energies on a regional level? This article argues that supra-regional conditions, such as law and financial support, are only one part of the story. Presented are the results of a case study in the east Cerman region of Lower Lusatia, a traditional energy region, where lignite surface mining is still an important economic factor. The case study focused on the views of re-gional actors in the field of renewable energies. From interviews with these actors, it became apparent that renewable energy activities are supported, or hindered, by: the involvement of regional pioneers and supporters, the regional mentality, the initial physical and socioeconomic situations, the availability of relevant information and know-how, regionally adjusted models and concepts, and regional cooperation. A central conclusion is that the supra-regional support of renewable energies should not only focus on technology but also on the activities of regional actors and on the factors that are decisive for the success, or failure, of their efforts to mobilise a sufficient number of comrades.
Regional Factors in the Development of Renewable Energies - Results of a Case Study in the Energy Region of Lower Lusatia.
Keywords: Versorgung; Energie; Energiegewinnung; Energieträger; Regionalwirtschaft; Braunkohlentagebau; Brachfläche; Alternativenergie; Energiepolitik; Förderungspolitik; Forschungsaufgabe; Befragung; Auswertungsmethode; Erneuerbare Energie; Einflussfaktor; Rahmenbedingung